Penerapan Asas Proporsionalitas Dalam Pemanfaatan Aset Negara Melalui Model Build Operate And Transfer/BOT - Kamilah, Anita (Jurnal Hukum & Pembangunan, 2020)
National development in infrastructure by utilizing state-owned assets is a priority of President Joko Widodo's administration in an effort to equalize people's welfare through ease of connectivity in all regions of Indonesia. The amount of Indonesia's foreign debt which reached Rp. 5,425 trillion as well as limited government funding in both the APBN and APBD, strived through collaboration with the private sector using the Build Operate and Transfer (BOT) model. For the government, infrastructure development through BOT provides benefits to be able to utilize state assets without having to spend funding, increase state revenue, and at the end of the BOT period can have adequate infrastructure and facilities and infrastructure. Likewise, the private sector can increase its business by entering into business fields that were previously monopolized by the government. In order to realize the implementation of the rights and obligations of the parties that are reciprocal and provide benefits to both parties, the implementation of the contract must be based on the principle of proportionality.